Pemanfaatan Sarana Prasarana Kerja, Self Capacity Building, dan Kinerja Tenaga Administrasi Sekolah Menengah Atas di Kota Medan - Simamora, Lusianna (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This research aims to examine the utilization of work infrastructure and self capacity building on the performance of school administrative staff. This research uses descriptive method with quantitative approach done to 109 school administration personnel. From the results of research conducted, the utilization of infrastructure facilities have a significant effect on the performance of school administrative staff on very high category. This can be explained by the high relation between the two dimensions of utilization of work infrastructure to the measured performance that is based on the principle and function of work infrastructure. Self capacity building also has a significant effect on the performance of school administrative personnel although it affects the middle category. This is identified by the low relation of five indicators of self capacity building to the performance of school administrative staff, ie workshop, seminar, courses, co- operative collegial development, and skill development model. The government should pay more attention to the availability, feasibility and convenience of work infrastructure and conduct various training aimed at the school administrative staff in an effort to increase the capacity building of school administration personnel to work.